جودة الحياة في العمل وعلاقتها بالاغتراب الوظيفي لدى أساتذة التعليم الثانوي - بوزيان محمد البشير; شمة الطاهر; بلمقدم فاطمة (My University, 2021)
This study aimed to identify the quality of life and its relationship to functional alienation, the sense of functional alienation, the quality of life by sex, age and professional experience in a study community of 49 professors, including 25 females and 24 males, and to achieve the objectives of this study we used a quality measure of life and a measure of functional alienation and data analysis we used spss and the results reached the following : •There is no correlation between the sense of job alienation and the quality of life of secondary school teachers. There are statistically significant differences among secondary school teachers by sex. •There are statistically significant differences among secondary school teachers by age. •There are statistically significant differences among secondary school teachers according to professional experience